2020
DOI: 10.1016/j.scitotenv.2019.134361
|View full text |Cite
|
Sign up to set email alerts
|

In situ fluorescence measurements of dissolved organic matter: A review

Abstract: There is a need for an inexpensive, reliable and fast monitoring tool to detect contaminants in a short time, for quick mitigation of pollution sources and site remediation, and for characterisation of natural dissolved organic matter (DOM). Fluorescence spectroscopy has proven to be an excellent technique in quantifying aquatic DOM, from autochthonous, allochthonous or anthropogenic sources. This paper reviews the advances in in situ fluorescence measurements of DOM and pollutants in various water environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(68 citation statements)
references
References 122 publications
(291 reference statements)
1
59
0
Order By: Relevance
“…Fluorescence measurement is inexpensive and reagentless and often requires little sample preparation; it is highly sensitive and non-invasive and allows the detection and characterisation of proteins, microorganisms, and inorganic, natural, and organic matter in water [62,68,72,73]. Fluorescence measurement instrumentation includes spectrofluorometers, microplate readers, fluorescence microscopes, fluorescence scanners (including microarray readers), and flow cytometers [36,69].…”
Section: Fluorescence Measurementsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fluorescence measurement is inexpensive and reagentless and often requires little sample preparation; it is highly sensitive and non-invasive and allows the detection and characterisation of proteins, microorganisms, and inorganic, natural, and organic matter in water [62,68,72,73]. Fluorescence measurement instrumentation includes spectrofluorometers, microplate readers, fluorescence microscopes, fluorescence scanners (including microarray readers), and flow cytometers [36,69].…”
Section: Fluorescence Measurementsmentioning
confidence: 99%
“…In contrast with standard water-testing procedures, the fluorescence measurement enables fast or near-instantaneous results, and it can be used with or without reagents, thus reducing costs; however, currently, for E. coli and enterococci, results can be delayed by sample collection, preprocessing, and fluorescence measurement in laboratories [8,38,74]. Furthermore, most typical fluorescence sensors are bulky and expensive and are commonly affected by optical inferences; findings have shown that miniaturisation, filters, and compensation algorithms could overcome such limitations, but more experimentation is required [62,72,73].…”
Section: Fluorescence Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Water of all kinds fluoresces [9], because only absorbing molecules can emit fluorescence. Carstea et al [12] have posited that fluorescence spectroscopy an inexpensive, reliable, excellent technique and fast monitoring tool is used to detect and quantify contaminants in a short time, for quick mitigation of pollution sources and site remediation, and for characterization of natural dissolved organic matter. In other words, fluorescence spectroscopy has proven to be an excellent technique in quantifying aquatic DOM, from autochthonous, allochthonous, or anthropogenic sources [38].…”
Section: Introductionmentioning
confidence: 99%